Identifying the hydrocarbon potential from seismic, geochemical, and wireline data of the Sallum intra-basin, North Western Desert of Egypt. Issue 1 (31st December 2023) - Badawy, M.; Abdel Fattah, Th. A.; Abou Shagar, S.; Diab, A. I.; Rashed, M. A.; Osman, M.
ABSTRACT: The current study's objectives are to identify the primary source rock's hydrocarbon potential and, using various approaches, examine the Sallum Concession's petroleum system, which lies in the extreme northwestern part of the Western Desert of Egypt. We integrated seismic, geochemical, and well logging data. As a result, the structure analysis indicates that the area is elevated topographic land, representing a high intra-basin about the surrounding Faghour, Matrouh, and Shushan basins. Therefore, the site is a significant concession with various source rocks; Khatatba (Safa member) and Alam El-Buieb (AEB-3A member) are the oil-prone source rocks of the northern and southern parts of the area with high TOC (up to 11.3%) and mid-mature stage (0.7-1.0% Ro) at depth below 8000 ft. On the other hand, the Paleozoic Desouqy, Zeitoun, and Shiffah formations, located below 12000 ft, are gas-prone source rocks with high organic contents (TOC 1.41-4.64%) and fair potential for gas generation and are currently in the mid-mature stage (0.7-1.0% Ro). We concluded that the concession's low oil production might result from a delay in Kerogen maturity and hydrocarbon migration. Finally, the East of Sallum concession is the only potential area because the wells in the west do not show reservoirs characteristics.